Microstructure And Compressive Properties Of Aluminum Foam Fabricated Using Sintering Dissolution Process - Suffin, Nur Surianni Ahamad (2011)
Sintering dissolution process (SDP) is a technique which enables fabrication of aluminum foam as a suitable absorber material with good quality. The aim of this research is to study the effect of various parameters towards morphology and compression properties of aluminum foam fabricated using SDP method. In this research, sodium chloride (NaCl) powders were used as space holder. Aluminum foams were fabricated using SDP method which involves milling (1 hour), compaction (200 MPa), sintering (570 ºC) and dissolution process (90 ºC). The first part of this research is to investigate the effect of different space holder content in aluminum foam on density, morphology, compression properties and energy absorption. The result shows that the space holder contributes to higher porosity and energy absorption which prevented the foam structure from collapsed during compression loading. In contrast, too high space holder content leading to high tendency of residual NaCl particles in aluminum foam which resulted in porous foam with lower compression properties and energy absorption. It was found that increasing dissolution time improved energy absorption due to complete dissolution of NaCl particles.